Psychologists' motivations for integrating apps into therapy with secondary school-aged young people. Issue 1 (21st October 2019) - Gindidis, Simone; Stewart, Sandra E.; Roodenburg, John
Abstract: Psychologists play an important role in the provision of mental health support to young people. Some psychologists are incorporating apps into therapy with young people; however, little is understood about why such incorporation is taking place. Ten semi-structured qualitative interviews exploring why psychologists augment therapy by recommending or using apps alongside therapy were undertaken. Findings suggest that psychologists were prompted to update their therapeutic approach in response to client-initiated discussion of apps. Personal use of apps, higher engagement in therapy, increased access to therapeutic strategies between sessions, and a reduction of the stigma associated with externalising therapeutic strategies were also facilitating factors. Implications for practice such as apps currently complementing structured therapy over unstructured talk therapy, and further research are explored.